Pharmaceutical Approaches on Antimicrobial Resistance: Prospects and Challenges - Firzan Nainu; Andi Dian Permana; Nana Juniarti Natsir Djide; Qonita Kurnia Anjani; Rifka Nurul Utami; Nur Rahma Rumata; Jianye Zhang; Talha Bin Emran; Jesus Simal-Gandara (MDPI AG, 2021)
The rapid increase in pathogenic microorganisms with antimicrobial resistant profiles has become a significant public health problem globally. The management of this issue using conventional antimicrobial preparations frequently results in an increase in pathogen resistance and a shortage of effective antimicrobials for future use against the same pathogens. In this review, we discuss the emergence of AMR and argue for the importance of addressing this issue by discovering novel synthetic or naturally occurring antibacterial compounds and providing insights into the application of various drug delivery approaches, delivered through numerous routes, in comparison with conventional delivery systems. In addition, we discuss the effectiveness of these delivery systems in different types of infectious diseases associated with antimicrobial resistance. Finally, future considerations in the development of highly effective antimicrobial delivery systems to combat antimicrobial resistance are presented.